Characteristics of Klebsiella pneumoniae harboring QnrB32, Aac(6’)-Ib-cr, GyrA and CTX-M-22 genes - Lianhua Yu; Jin Zhang; Yong Liang; Yongxiao Qi; Haibao Wang; Dongguo Wang (Folia Histochemica et Cytobiologica, 2012)
Quinolone resistance in members of the Enterobacteriaceae family is mostly due to mutations in the quinolone resistance-determining regions of topoisomerase genes. CTX-M-22 is a member of the CTX-M family which can reduce extended-spectrum β-lactamase (ESBL) production and modulate antibiotic resistance, resulting in low ceftazidime minimum inhibitory concentrations (MICs). There are four different genes in Klebsiella pneumoniae (KP4707) including qnrB32 (novel qnr allele gene, HQ704413), aac(6’)-Ib-cr (novel aac(6’)-Ib allele gene, HQ680690), gyrA (novel gyrA allele gene, HQ680691) and CTX-M-22 gene. Five point amino acid mutations Arn(N)27 → Leu(L), Val(V)129 → Ala(A), Iie(I)142 → Met(M), Gly(G)188 → Arg(R), Val(V)212 → Iie(I) were observed in the qnr32 gene when compared to qnrB1. Of all qnrB alleles, a novel variant of the qnrB32 gene, with qnrB31, had the highest amino acid homology. Three point amino acid mutations including Trp(W)105 → Arg(R), Asp(D)182 → Tyr(Y) and Val(V)201 → Asp(D) were observed in aac(6’)-Ib-cr gene, when compared to GenBank number AF479774. New variants of qnr32, aac(6’)-Ib-cr, gyrA and CTX-M-22 or other genotype determinants continuously appear in different genomic sites and also outside the Enterobacteriaceae family.